A qualitative study of maternal and paternal parenting knowledge and practices in rural Mozambique - Ahun, Marilyn N.; Bliznashka, Lilia; Karuskina-Drivdale, Svetlana; Regina, Gino; Yousafzai, Aisha K.; Jeong, Joshua (BioMed Central, 2024)
Background: Providing nurturing care for young children is essential for promoting early child development (ECD). However, there is limited knowledge about how mothers and fathers across diverse contexts in sub-Saharan Africa care for their children and from whom they receive guidance and support in their caregiving roles. We aimed to examine caregivers’ nurturing care practices and sources of parenting knowledge in rural Mozambique.